Toxic waste trade with less-industrialized countries : economic linkages and political alliances. - CLAPP, Jennifer (1994)
Outlines how international trade, production, and financial relationships have determined the direction and extent of the toxic waste trade with less-industrialized countries. Shows that the waste trade in turn has not only negatively affected the environments of many of these countries, but also threatens their future economic prospects. Argues that by linking up with Third World States to fight for a waste trade ban, NGOs were able to exert a great deal of influence over the outcome of the Basel Convention on the Transboundary Movement of Hazardous Waste and Disposal.